Internext revista eletrônica de negócios internacionais da ESPM. (Programa de Mestrado em Gestão Internacional da ESPM, Escola Superior de Propaganda e Marketing, 2006)
"InternexT, Revista Eletrônica de Negócios Internacionais Internext, Electronic Journal of International Business, is published three times a year by the Programa de Mestrado em Gestão Internacional da ESPM -- Escola Superior de Publicidade e Marketing - Master in International Management Programme of ESPM -- Superior School of Advertising and Marketing - and it constitutes itself as an editorial space which is open to the whole national and international scientific community that is interested in the discussion of questions related to the development of this domain in Brazil. The journal focuses on publications of researches and reflections in the area of International Business, with topics that cross the various areas of management: strategy, finances, people management, organisational studies, among others. Our editors dedicate their prestige to the seriousness of the work of the journal, and our scientific committee works within the academic proceedings in order to assure the quality of the published articles, of the referees' reports which are sent to the authors, of the interest and of the innovation and of the reliable source of the research the readers are provided with. With this initiative, we hope to render a significant service to the scientific community and to be up to the mark of our institution."--Focus and scope.